Litteratur - Ivar Agge; Erik Christensen; Louis Le Maire; Carl Holmberg; Erik M. Martens; Harry Söderman; Arne Björk; Knud Waaben; Brynolf Honkasalo; F.J.R. Andrén; Stephan Hurwitz; F.v. Magins (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews